O terciário (re) desenhando a periferia: a região administrativa norte de Natal/RN, na última década do século XX, servicializada na Av. Dr. João Medeiros Filho - Souza, Rosa de Fátima Soares de (2008)
The tertiary sector has been (re)defining and (re)qualifying, in an impacting way, the urban spaces in the cities, introducing new elements for the discussion of the relationship center/periphery. In Natal, as an inducing economic activity of its development, it conforms to the new needs of the capital, expanding, being materialized through several processes and spatial forms. We aim at analyzing one of those processes, which has taken its Northern Administrative Area to (re)define the design of its urban space, through the actions developed by the agents involved with the spatialization of the tertiary activities, at the same time as it redimensions its role as a periphery of Natal, contributing to the study of the recent and growing transformations of the Brazilian capitals. The studied district corresponds to 39.4% of the municipal area and, until recently, was composed by precarious reproduction spaces, unprovided of relevant economical activities. After the boom of the development of extensive housing complexes by SFH/BNH, the area, gradually stopped being a dependent area, and it imposed itself as an economically participant region, with the increase of the trade and services sectors, as well as a favorable place for the appearance of new activities. Its reflexes are noticeable in the achieved spatial configuration. As the main road to induct changes, Dr. João Medeiros Filho Avenue presents these new tendencies in the production of the intraurban space, concentrating the largest goods and services equipments of the area, through investments of the private and public sectors, which guarantee the capital allocation for the construction of a new centrality